IMPLIKASI PUTUSAN TALAK VERSTEK TERHADAP HAK NAFKAH MANTAN ISTRI (ANALISIS PUTUSAN PENGADILAN AGAMA KARANGANYAR) - Sangidun, Muhammad; Rosidah, Zaidah Nur (LPPM STAI DARUSSALAM LAMPUNG, 2024)
Article 149 KHI provides protection of rights to wives who are divorced through talak divorce. This protection is in the form of an obligation for ex-husbands to provide iddah and mut'ah maintenance whether this is requested or given by the judge through his ex officio rights. However, in decision number 1288/Pdt.G/2020/PA.KA. Karanganyar Religious Court, the judge decided not to grant the claim for maintenance rights even though the plaintiff was also a wife who was divorced by divorce. This research focuses on exploring the judge's reasons for rejecting the charge, as a form of judge's interpretation of the provisions of Article 149 KHI regarding case number 1288/Pdt.G/2020/PA.KA. The data in this study were obtained through primary sources of interviews with judges examining cases, as well as secondary data in the form of legal materials to find out the concrete considerations of judges in trials in the form of copies of decision number 1288/Pdt.G/2020/PA.KA and decision number 348/Pdt. G/2020/PA. Smn. The data in this study were processed and displayed in the form of descriptions, as well as analysis using deductive methods. The examining judge for case 1288/Pdt.G/2020/PA.KA interpreted the provisions of Article 149 KHI as an imperative, but limited obligation. This means that the wife's rights can be invalidated for several reasons, including because of the nusyuz wife or the absence of the wife during the divorce trial. In deciding cases, Keyword: Divorce; Iddah; Mut’ah; Living; Verstek